A new strategy to destroy cancer cells using osmium dioxide (OsO2) and osmium tetroxide (OsO4) nanoparticles and magnetic fields under synchrotron and synchrocyclotron radiations - Heidari, Alireza; Hotz, Margaret; MacDonald, Nancy; Peterson, Victoria; Caissutti, Angela; Besana, Elizabeth; Esposito, Jennifer; Schmitt, Katrina; Chan, Ling-Yu; Sherwood, Francesca; Hendrson, Maria; Kimmel, Jimmy (International Journal of Advanced Chemistry, 2021)
In the current research, a new strategy to destroy cancer cells using Osmium Dioxide (OsO2) and Osmium Tetroxide (OsO4) nanoparticles and magnetic fields under synchrotron and synchrocyclotron radiations is investigated. The calculation of thickness and optical constants of Osmium Dioxide (OsO2) and Osmium Tetroxide (OsO4) a new strategy to destroy cancer cells using Osmium Dioxide (OsO2) and Osmium Tetroxide (OsO4) nanoparticles and magnetic fields under synchrotron and synchrocyclotron radiations produced using sol–gel method over glassy medium through a single reflection spectrum is presented. To obtain an appropriate fit for reflection spectrum, the classic Drude–Lorentz model for parametric di–electric function is used. The best fitting parameters are determined to simulate the reflection spectrum using Lovenberg–Marquardt optimization method. The simulated reflectivity from the derived optical constants and thickness are in good agreement with experimental results.   A new strategy to destroy cancer cells using Osmium Dioxide (OsO2) and Osmium Tetroxide (OsO4) nanoparticles and magnetic fields under synchrotron and synchrocyclotron radiations
Keywords: Cancer Cells; Osmium Dioxide (OsO2) and Osmium Tetroxide (OsO4) Nanoparticles; Magnetic Fields; Synchrotron and Synchrocyclotron Radiations.